Pengembangan Video Powerpoint Tutorial Dalam Pembelajaran Tematik Kelas II SD Muhammadiyah 2 Pontianak - Andika Putri Sabrina; Bistari Bistari; Siti Halidjah; Suparjan Suparjan (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
During the Covid-19 pandemic, learning process cannot be done by face-to-face so teachers are required to be creative in choosing learning media. Based on these problems, a video powerpoint tutorial product was developed in the thematic learning for the Second Grade of Muhammadiyah Elementary School 2 Pontianak in order to describe the results of validation and student responses.. The research design used in this research was Research and Development (RnD) by utilizing 4D theory from Thiagarajan that consisted of 4 steps such as define, design, develop, and dissemination. The product of this research and development was a PowerPoint Tutorial Video for Thematic teaching and Learning in which the validity had been tested by the experts. The result from the experts' validation proposed that the product scored 91.25% for its advisability in the aspect of teaching & learning (materials), 88.75% in the aspect of its media (display), and 72.5% in the aspect of language. Furthermore, the simplicity of this product also had been tested based on the 60 students' responses with the average score 3.37 in percentage of 84%. Therefore, according to the students’ responses score, it can be concluded the product was considered good and advisable to use.